2009
DOI: 10.1073/pnas.0907409106
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase negatively regulates hydrogen peroxide-stimulated AMP-activated protein kinase in endothelial cells

Abstract: mice; pooled data are also shown. * , P Ͻ 0.05; ** , P Ͻ 0.01; *** , P Ͻ 0.001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 46 publications
0
28
1
1
Order By: Relevance
“…42 H 2 O 2 could activate endothelial AMPK through Ca 2+ / CaM-dependent protein kinase β pathway within its physiological concentrations, which could be a possible important feedback mediator of AMPK. 43 In the present study, we found that vascular smooth muscle cell hyperpolarization of mesenteric arteries (in the presence of NO and prostacyclin inhibitors) was significantly impaired in eAMPK-KO mice with reduced relaxation responses, indicating that eAMPK is substantially involved in EDH responses. …”
Section: Endothelial Ampk Mediates Edhmentioning
confidence: 53%
“…42 H 2 O 2 could activate endothelial AMPK through Ca 2+ / CaM-dependent protein kinase β pathway within its physiological concentrations, which could be a possible important feedback mediator of AMPK. 43 In the present study, we found that vascular smooth muscle cell hyperpolarization of mesenteric arteries (in the presence of NO and prostacyclin inhibitors) was significantly impaired in eAMPK-KO mice with reduced relaxation responses, indicating that eAMPK is substantially involved in EDH responses. …”
Section: Endothelial Ampk Mediates Edhmentioning
confidence: 53%
“…The HyPer2 H 2 O 2 biosensor yields an increase in fluorescence that is highly specific for H 2 O 2 . This biosensor has been characterized extensively in vitro and in cultured cells (29,(31)(32)(33). We isolated cardiac myocytes from mice after tail vein injection with the HyPer2 lentivirus and analyzed changes in cell-derived fluorescence after treating the cells with H 2 O 2 , Ang-II, or isoproterenol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using the H2O2 biosensor, HyPer, 103 showed that eNOS knockdown led to increased H2O2 and AMPK phosphorylation in endothelial cells. 101 Clearly, there is a close interplay between physiological levels of H2O2 and eNOS-dependent signaling pathways (Figure 7). Higher H2O2 concentrations appear to have broader effects on oxidant-modulated signaling pathways.…”
Section: Akt-and Ampk-dependent Enos Phosphorylationmentioning
confidence: 99%